Unpacking the NIH Toolbox Emotion Battery in Persons With Parkinson's disease. (29th November 2022) - Lopez, Francesca V; Schade, Rachel; Ratajska, Adrianna; Kenney, Lauren; Rodriguez, Katie; Ray, Alyssa; Santos, Lauren; Scott, Bonnie M; Trifilio, Erin; Bowers, Dawn
Abstract: Objective: Examine the relationship between the National Institutes of Health Toolbox Emotion Battery (Emotion Toolbox) and traditional measures in Parkinson's disease (PD). Method: Persons with PD ( n  = 30) and cognitively healthy older adults (OA; n  = 40) completed the Emotion Toolbox consisting of Well-Being, Negative Affect, and Social Satisfaction scores along with traditional measures of depression (Beck Depression Inventory-II [BDI-II]), anxiety (State–Trait Anxiety Inventory [STAI]), and apathy (Apathy Scale [AS]); total raw scores). Results: Separate bootstrapped analyses of covariance indicated that the PD group scored higher on BDI-II and STAI-State compared to OA ( p s < .01); groups did not differ on Emotion Toolbox. In the PD group, bootstrapped partial correlations indicated that Negative Affect was positively related to BDI-II and STAI ( p s ≤ .001). Social Satisfaction was negatively related to BDI-II and STAI-Trait (.05 <  p s < .004). Psychological Well-Being was negatively related to BDI-II, AS, and STAI ( p < .004). No relationships emerged in OA. In the PD group, separate binary logistic regressions showed that traditional measures (BDI-II, AS, and STAI-Trait) correctly classified 79.6% those with formal psychiatric diagnoses (presence vs. absence; p  < .011), whereas Emotion Toolbox measures correctly classified 73.3% ( p  < .019). Conclusions: The Emotion Toolbox showed moderate-strong correlations with traditional measures in persons with PD. Even so, it did not capture the group differences between PD and OA and had a somewhat lower classification accuracy rate for persons with PD who had a formal psychiatric diagnosis than traditional measures. Together, findings question the utility of the Emotion Toolbox as a stand-alone emotion screener in PD.